Comparative Analysis of Pseudo-nitzschia Chloroplast Genomes Revealed Extensive Inverted Region Variation and Pseudo-nitzschia Speciation - He, Ziyan; Chen, Yang; Wang, Yichao; Liu, Kuiyan; Xu, Qing; Li, Yang; Chen, Nansheng (Frontiers in Marine Science, 2022)
Pseudo-nitzschia is a species-rich genus where many species can induce harmful algae blooms (HABs) associated with the toxin domoic acid (DA) production. Despite the importance of Pseudo-nitzschia species to coastal environments, their genomic information is rather limited, hindering research on biodiversity and evolutionary analysis. In this study, we report full-length chloroplast genomes (cpDNAs) of nine Pseudo‐nitzschia, among which cpDNAs of eight Pseudo-nitzschia species were reported for the first time. The sizes of these Pseudo-nitzschia cpDNAs, which showed typical quadripartite structures, varied substantially, ranging from 116,546 bp to 158,840 bp in size. Comparative analysis revealed the loss of photosynthesis-related gene psaE in cpDNAs of all Pseudo-nitzschia species except that of P. americana, and the selective loss of rpl36 in P. hainanensis. Phylogenetic analysis showed that all Pseudo-nitzschia strains were grouped into two clades, with clade 1 containing cpDNAs of P. multiseries, P. pungens, P. multistriata, and P. americana, and clade 2 containing cpDNAs of P. hainanensis, P. cuspidata, Pseudo-nitzschia sp. CNS00097, P. delicatissima, and P. micropora. The small size of the P. americana cpDNA was primarily due to its shortened inverted repeat (IR) regions. While psaA and psaB were found in the IR regions of cpDNAs of other eight species, these two genes were found outside of the IR regions of P. americana cpDNA. In contrast, P. hainanensis had the largest size because of expansion of IR regions with each IR region containing 15 protein-coding genes (PCGs). Eleven genetic regions of these Pseudo-nitzschia cpDNAs exhibited high nucleotide diversity (Pi) values, suggesting that these regions may be used as molecular markers for distinguishing different Pseudo-nitzschia species with high resolution and high specificity. Phylogenetic analysis of the divergence of nine Pseudo-nitzschia species indicated that these species appeared at approximately 41 Mya. This study provides critical cpDNA resources for future research on the biodiversity and speciation of Pseudo-nitzschia species.